Global consortium for the classification of fungi and fungus-like taxa - Hyde, Kevin David (2023)
The series Outline of Fungi and fungus-like taxa (including fossil fungi) commenced with its first publication in 2020, has garnered over 450 citations to date, and is proving to be a very important publication in fungal classification. Since the inaugural outline by Wijayawardene et al. (2020a), we have strived to improve the effectiveness and accuracy of the outline, and this resulted in an updated 2022 outline (Wijayawardene et al. 2022a) featuring contributions from 57 authors. Nevertheless, worldwide participation was not sufficient to overcome arguments that the outline was not representative of most mycologists. Therefore, in 2022, we launched the Global Consortium for the Classification of Fungi and fungus-like taxa and its associated webpage, outlineoffungi.org, and invited numerous interested parties from around the world to form an internationally representative consortium. In this paper, we have more than 550 members representing 55 countries with a range of disciplines, providing a balanced participation in the Global Consortium for the Classification of Fungi and fungus-like taxa. As the project progresses, we will publish the Outline of Fungi and fungus-like taxa biannually, with notes on new taxa at or above the level of species. Along with the updated classification scheme for fungi and fungus-like taxa, any notes, critiques, or remarks on controversial topics, especially those pertaining to taxonomy and the establishment of novel taxa, will also be included. Where possible, we will provide appropriate parties with opposing arguments or any clarifications on these topics. Given the dynamic nature of fungal taxonomy as a field of study, it undergoes frequent updates and revisions as new data is acquired from various disciplines such as biochemistry, ecology, evolution, genomics, genetics, morphology, metabolomics, transcriptomics, phylogenetics, physiology, and proteomics. These advancements contribute to the modification of classification and taxonomic concepts at different taxonomic hierarchy. Therefore, it is essential to publish an Outline of Fungi and fungus-like taxa biannually to stay up-to-date on the changes and provide a universal platform to discuss controversial topics.